Sibling Relationship Quality and Loneliness Among Adolescents Living with Siblings with Special Needs - Nadia, Fazila; Kusumaningrum, Fitri Ayu (Unisia, 2025)
Adolescence is a critical developmental period in which social relationships play a central role in psychological well-being, and adolescents who live with siblings with special needs, often referred to as glass children, may be particularly vulnerable to loneliness. This study aimed to examine the association between sibling relationship quality and loneliness among adolescents who have and live with siblings with special needs. Using a quantitative correlational design, data were collected from 87 adolescents aged 12 to 18 years through purposive sampling. Loneliness was measured using the UCLA Loneliness Scale Version 3, while sibling relationship quality was assessed with the Sibling Relationship Questionnaire, covering warmth and closeness, power, conflict, and rivalry. Correlational analyses were conducted using Pearson and Spearman methods following tests of normality and linearity. The results indicated a significant negative association between warmth and closeness in sibling relationships and loneliness, suggesting that higher emotional closeness and affection between siblings are linked to lower levels of loneliness among glass children. In contrast, the dimensions of power, conflict, and rivalry showed weak and statistically non-significant relationships with loneliness, although their directional patterns varied. Additional analyses revealed that female adolescents reported significantly higher levels of loneliness than males, while no significant differences were found based on age group or birth order. Overall, the findings highlight the central role of emotional warmth and closeness in sibling relationships as a protective factor against loneliness in adolescents living with siblings with special needs. These results underscore the importance of fostering supportive sibling interactions within families as part of efforts to promote adolescent mental health in this population.